Understanding tourist mobile hotel booking behaviour: Incorporating perceived enjoyment and perceived price value in the modified Technology Acceptance Model - Mohamad Amiruddin Mohamad; Mohd Hafiz Hanafiah; Salleh Mohd Radzi (Tourism & Management Studies)
This study examines how mobile technology adoption influences customers' intention to book hotel rooms via smartphone. This study empirically incorporated perceived enjoyment and perceived value in the modified Technology Acceptance Model (m-TAM) and tested it as a unified model. Partial Least Square-Structural equation modelling (PLS-SEM) was applied to estimate the proposed research framework based on the survey data collected from 386 travellers who booked hotels via their smartphones. The structural model confirms perceived usefulness, perceived ease of use, perceived enjoyment, and perceived price value significantly influence consumers' behavioural intentions toward mobile hotel booking. This study confirms that TAM can be extended and employed to predict and explain the acceptance of the new technologies in service industries. This study also provides valuable theoretical contributions in developing and testing related theories and practical implications to hotel operators, online travel agencies (OTAs), and hospitality technology suppliers.